2018
DOI: 10.5114/wo.2018.73885
|View full text |Cite
|
Sign up to set email alerts
|

Surface markers of cancer stem-like cells of ovarian cancer and their clinical relevance

Abstract: Cancer stem-like cells (CSLCs) are defined as cancer cells with stem cell characteristics. Although CSLCs constitute no more than a few percent of the tumor mass, they play important roles in cancer chemo-resistance, metastasis and disease recurrence. Ovarian cancer (OC) is considered the most aggressive gynecological malignancy in which the role of CSLCs is of major significance, although it remains to be specified. The studies describing ovarian CSLC phenotype vary in the definition of the molecular pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 66 publications
(77 reference statements)
0
48
0
1
Order By: Relevance
“…So far, no universal marker combination has been found to faithfully indicate ovarian cancer stem-like cells (CSLC), although surface proteins CD44 and CD133 are proposed by several authors (reviewed in: [ 24 , 25 ]). Flow cytometry (FC) detection of CD44 and CD133 showed that the majority of ovarian cancer lines tested contained approximately 0.1% of CD44+/CD133+ cells (putative CSLC).…”
Section: Resultsmentioning
confidence: 99%
“…So far, no universal marker combination has been found to faithfully indicate ovarian cancer stem-like cells (CSLC), although surface proteins CD44 and CD133 are proposed by several authors (reviewed in: [ 24 , 25 ]). Flow cytometry (FC) detection of CD44 and CD133 showed that the majority of ovarian cancer lines tested contained approximately 0.1% of CD44+/CD133+ cells (putative CSLC).…”
Section: Resultsmentioning
confidence: 99%
“…is commonly used as a stem cell marker in combination with CD117, MyD88, E-cadherin/CD34, and CD24/EpCAM. Each of these CD44 + cell populations has been demonstrated to have stem-like properties (reviewed in Klemba et al) 78 . In conclusion there are multiple surface markers used to identify CSCs in ovarian cancer.…”
Section: Cell Surface Markersmentioning
confidence: 99%
“…Cluster 6 highly expressed vimentin and Ki-67 along with comparatively lower expression of EMT markers (ZEB1 and ZEB2), suggestive of cells undergoing mesenchymal to epithelial transition (Figure 3E). Ovarian cancer stem cells marked by co-expression of CD33, CD44, CD117 and CD24 expression were not observed 32 . Cells in this cluster expressed IL-6 which correlates with poor prognosis in ovarian cancer and TGF-β which induces an aggressive cancer phenotype 3336 .…”
Section: Resultsmentioning
confidence: 95%